Clinical characteristics and outcomes of patients with inflammatory and autoimmune rheumatological diseases admitted for intensive care in Colombia - D.G. Fernández-Ávila; Ó.R. Vargas-Vanegas; L. Galindo-Rozo; Á. García-Peña; Ó. Muñoz-Velandia (PAGEPress Publications, 2023)
Objective. Contemporary studies reporting outcomes of critical care in patients with inflammatory and autoimmune rheumatological diseases are scarce. This study describes 15 years of experience from 2005-2019 in a Colombian referral hospital. Methods. This observational, descriptive, consecutive case series study was performed on adult patients with inflammatory and autoimmune rheumatic diseases who were admitted to the intensive care unit (ICU) of the San Ignacio University Hospital in Bogotá (Colombia), from January 1, 2005, to December 21, 2019. We describe the sociodemographic characteristics, admission causes and criteria, lengths of stay, immunosuppressive treatment, systemic support, and mortality. Results. The study included 300 patients with a median age of 48 years [interquartile range (IQR) 31-62 years], predominantly female (76%). Disease exacerbations (30%), infections (17.6%), and cardiovascular diseases (15%) were the main causes of admission. Respiratory failure (23%) most commonly caused by septic shock (24%) was the principal indication for intensive care admission. The most frequent infections were community-acquired pneumonia (11.6%) and soft-tissue infections (9%). In 40.3% of patients, inotropic and vasopressor support was required. The median length of stay was 4 days (IQR 2-8), and global mortality was 21.6%. Conclusions. Rheumatic diseases in the ICU are still associated with high morbidity and mortality. Patients with inflammatory and autoimmune rheumatic diseases require a meticulous clinical approach, strict clinical monitoring, frequent assessment of complications, evaluation of systemic support needs, and specific management.